The Ethical Limitation of Using Artificial Intelligence (AI) in Teaching Prophetic Tradition - Mufid, Abdul (Jurnal Ushuluddin, 2024)
This research explored the relationship between Prophetic traditions and artificial intelligence (AI), focusing on the ethical implications and dynamics of human-AI interactions in the context of hadith teachings in the postmodern technological era. Involving an in-depth analysis of the Prophet's teachings regarding science and technology, this research aims to detail ethical perspectives that can guide the development and use of artificial intelligence. With an interdisciplinary approach, this research combined religious values with developments in AI technology, discussing the confluence between the traditions of the Prophet and current dynamics in the world of technology. Ethical implications from an Islamic hadith perspective were detailed, highlighting how moral and human values could be integrated into designing and implementing AI technologies. Additionally, this research explored the impact of human-AI interactions in the postmodern era, considering how AI technology could support the development of a society based on the Prophet's teachings and values. A comprehensive understanding of artificial intelligence's limitations, risks, and human responsibilities was also detailed to balance technological progress and moral values. Hopefully, the research results will contribute to a better understanding of the relationship between religious traditions, especially hadith teachings, and advances in AI technology, providing a solid ethical foundation for technological development in the postmodern era